Influence of Heat Exchanger Tube Layout on Performance of Heat Pump System for Electric Cars. (May 2017) - Zhang, Xiaoqiang; Xue, Qingfeng; Zou, Huiming; Liu, Jixuan; Tian, Changqing; Zhang, Xuelai
Abstract: The external micro-channel heat exchanger plays a significant role in performance of the heat pump system for EVs. It functions as both the evaporator and condenser. A test bench with the heat pump system is set up to research the influence of arrangement (vertical or horizontal) of flat tubes on the system performance. The investigation results show: on heating conditions, the horizontal HX has greater pressure drop, which brings about less heat absorption, higher compressor power consumption and worse system COP. However, the vertical HX is easier to frost than the horizontal. On cooling conditions, the heat pump system with horizontal external HX has larger cooling capacity and better COP.